Analisis Dampak Penerapan Bilingual Learning Dalam Kemampuan Berkomunikasi Bilingual Peserta Didik Di Sd Unggulan Hamzanwadi - Kasturi, B. Nining; Nursaly, Baiq Rismarini; Murcahyanto, Hary (Universitas Hamzanwadi, 2024)
This study aims to analyze the impact of bilingual learning implementation on the bilingual communication skills of students at SD Unggulan Hamzanwadi. The method used is a qualitative approach with purposive sampling technique, involving teachers and students. The results show that the implementation of bilingual learning enhances students' communication skills both in school and outside school. Students feel more confident in communicating in English. However, challenges exist, such as shy students and the acclimatization of new students. In conclusion, the bilingual learning program positively contributes to students' language abilities.